CRAFTING A SURVEY INSTRUMENT FOR EDUCATIONAL PODCASTS: INTEGRATING TECHNOLOGY IN ENGLISH LANGUAGE TEACHING ENHANCEMENT - Inderawati, Rita (University of Kuningan, 2024)
One technology that is increasingly popular in education is podcasts, which present an engaging and accessible format for delivering learning material. Despite their popularity, there is a lack of research on measuring instruments for educational podcasts. This study aims to produce a valid questionnaire to assess students' perspectives on educational podcast creation in the context of integrating technology in English language teaching. By reviewing the literature, four important aspects of educational podcast creation were identified. The research resulted in 60 statements covering these key aspects. The validity of the instrument was tested through assessments by English language education experts, producing valid results. The validation process involved evaluating statement items qualitatively, considering relevance, feasibility, and suitability to the research objectives. This instrument is expected to contribute significantly to improving English language learning through technology and student collaboration.